Can Ileostomy Reversal Be Safely Performed by Surgical Residents? - Michał Kisielewski; Magdalena Pisarska-Adamczyk; Natalia Dowgiałło-Gornowicz; Łukasz Nawacki; Wojciech Serednicki; Mateusz Wierdak; Jerzy Wilczek; Kamil Safiejko; Marcin Juchimiuk; Marian Domurat; Jacek Pierko; Mateusz Mucha; et al. (Medicina)
Background and Objectives: The growing number of colorectal cancer patients has highlighted the importance of surgical education in colorectal surgery. Despite the negative impact of the COVID-19 pandemic on surgical training, recent changes in the Polish surgical training program have increased the number of intestinal procedures required to be completed by residents. This study aims to assess the safety of ileostomy reversal procedures performed by surgical residents. Materials and Methods: A multicenter prospective cohort study, the LILEO study, was conducted from October 2022 until December 2023 across 20 Polish surgical departments. The study included 199 patients who underwent ileostomy reversal and were divided into two groups: 139 patients operated by specialist surgeons and 60 patients operated by surgical residents. The primary outcomes measured were postoperative complications, length of hospital stay (LOS), and 30-day reoperation rate. Secondary outcomes included the severity of perioperative complications assessed using the Clavien–Dindo classification and a focused analysis of loop ileostomy reversal outcomes. Results: The median LOS was significantly shorter in the resident group (5.5 days vs. 6 days, p < 0.05). Although the overall complication rate was lower in the resident group (21.7% vs. 33.1% in the specialist surgeon group), this difference was not statistically significant (p = 0.105). The 30-day reoperation rate was 3.3% in the resident group and 8.6% in the specialist surgeon group (p = 0.179). In terms of severity, minor complications (Clavien–Dindo grades 1 and 2) were more common in the specialist group (p < 0.05). The analysis of loop ileostomy reversals revealed no significant differences in postoperative outcomes between the two groups. Conclusions: Ileostomy reversal procedures performed by surgical residents under supervision are safe and feasible, with outcomes comparable to those performed only by specialist surgeons. These findings support ileostomy reversal as a valuable procedure for developing surgical residents’ skills and do not negatively affect postoperative outcomes.